Design And Implementation Of Ls-Pmsg For Small Scale Hydro Power Plant - Yusuf Ismail Nakhoda; Feri Prasetyo Nugroho; M. Abd. Hamid; Awan Uji Krismanto; Eko Yohanes Setiawan (Widyagama University of Malang, 2018)
- In conventional power system, synchronous generator which characterized by high-speed operating condition has been widely implemented. However, those high-speed synchronous machines are not suitable for a power plant powered by renewable energy (RE) due to uncertain feature of renewable resources. To overcome this problem, an electrical machine with low-speed characteristic is required for ensuring stable operation and maintaining output power of the RE based distribution generation (DG) unit. In this paper, a low-speed permanent magnet synchronous generator (LS-PMSG) is designed and implemented. To realize low-speed operation capability, the multi-stages permanent magnet synhcronous machine is proposed. The multi-stages machine equipped with two stators and three rotors construction. From the experimental results, it was monitored that output voltage of single rotor of the designed machine was 35 V. Moreover, to increase the output voltage to 50 V, those three rotors can be connected in series.